Evaluation of Demirjian stage of the third molar as a reliable predictor of 18 years age - Kumar, Pramod; Kumari, Soni; Priya, Nimisha; Shekhar, Arpita; Kumar, Krishna; Kumar, Ashish (International Journal of Research in Medical Sciences, 2024)
Background: In accordance with section 3(1) of the 1875 Indian majority act, any individual residing in India must reach the majority age when they reach the age of 18 and not before. Third molar formation begins approximately the age of 18. This study aims to distinguish the third molar Demirjian stage(s) indicate that the individual is under the age of 18, and which do not, we will be able to determine the person’s age. Methods: In this research, 202 patients’ OPG radiographs aged 14-25 years were obtained. Their radiographs revealed 742 third molars in total. Third molar development was examined using Demirjian’s eight-stage method, and average age was then calculated for each step of third molar growth. Stages under the age of eighteen and stages over the age of eighteen were analyzed. Results: Data revealed that a person was in stage C most likely under the age of 18 (minor) and at stage H, a person was most likely over the age of 18 (major). Stages A and B were not evident in the age range studied. The age associated with stage C was less than 18 years, while the age associated with stage H was greater than 18 years. Conclusions: Assessing third molar growth stages is a reliable non-invasive method for estimating an individual’s age. Stage H indicates a likely age over 18 with completed root development, while stage C suggests an age under 18 with ongoing root development, making it a quick and useful approach.